2022
DOI: 10.3389/fonc.2022.848199
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Candidate miRNAs, Its Targeted Genes and Pathways in Chronic Myeloid Leukemia–An Integrated Bioinformatical Analysis

Abstract: Chronic myeloid leukaemia is blood cancer due to a reciprocal translocation, resulting in a BCR-ABL1 oncogene. Although tyrosine kinase inhibitors have been successfully used to treat CML, there are still cases of resistance. The resistance occurred mainly due to the mutation in the tyrosine kinase domain of the BCR-ABL1 gene. However, there are still many cases with unknown causes of resistance as the etiopathology of CML are not fully understood. Thus, it is crucial to figure out the complete pathogenesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Therefore, a decrease in miR-21 expression may be considered beneficial in promoting apoptosis and cell death. In the context of chronic myeloid leukemia (CML), miR-21 has been extensively studied as an important regulator of gene expression that may influence the efficacy of tyrosine kinase inhibitors (TKIs) commonly used in to treat CML [ 40 ]. Previous research by Alves et al has shown that low miR-21 levels at the time of CML diagnosis are associated with a better response to TKI therapy, making it an attractive target for drug therapy [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a decrease in miR-21 expression may be considered beneficial in promoting apoptosis and cell death. In the context of chronic myeloid leukemia (CML), miR-21 has been extensively studied as an important regulator of gene expression that may influence the efficacy of tyrosine kinase inhibitors (TKIs) commonly used in to treat CML [ 40 ]. Previous research by Alves et al has shown that low miR-21 levels at the time of CML diagnosis are associated with a better response to TKI therapy, making it an attractive target for drug therapy [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of miRNAs in CLL prognosis has been investigated in various research. as well as other research groups, have examined miRNAs in CLL patients with overexpression of ZAP70 and unmutated IGHV gene; they reported a significant association between the overexpression of miR‐15a, miR‐16‐1, miR‐16‐2, miR‐23b, miR‐24‐1, miR‐146, miR‐155, miR‐195, miR‐221, and down‐expression of miR‐223, miR‐29a‐2, miR‐29b‐2, and miR‐29c with unmutated IGHV gene, high expression of ZAP70, and unfavorable prognostic in CLL cases [121‐123]. Another study conducted by Due et al.…”
Section: Introductionmentioning
confidence: 94%
“…Increased expression of miR-362-5p as oncomiR through GADD45a down regulation and decreased expression of miR-320a as tumour suppressor through PI3K/AKT and NF-kb pathway are involved in the migration and invasion pathway ( 43 ). In this way, increasing the expression of miR-320a by inhibiting the phosphorylation of mentioned pathways leads to weakening the oncogenic function of bcr/abl ( 44 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, increasing its expression in THP-1 human leukaemia monocytic cell line produces the opposite result. By targeting DAB2, miR-93 inhibits the PI3K/AKT signalling pathway and increasing DAB2 expression negatively affects the growth of THP-1 cells ( 44 ). miR-125a acts as a tumour suppressor in patients with leukaemia.…”
Section: Introductionmentioning
confidence: 99%